Older Knowledge Workers as the Labour Market Potential (Slovenia versus Finland) - Zupančič, Magda (Naše gospodarstvo/Our economy, 2016)
This article refers to the challenge of demographic changes gaining attention in many developed countries. The European Union recognized the need to activate older knowledge workers, who are underrepresented and pushed out of the labour market or are inadequately motivated to continue their employment for various reasons, despite their accumulated knowledge and experiences. EU member states respond differently to their ageing, with more or less successful national policies. This article is based on research of the labour market development for older knowledge workers in Slovenia compared to the Finnish age management policy at the end of the 1990s that successfully increased Finnish older knowledge workers’ employment through focused and holistic measures. Slovenia stagnated in the same period due to a lack of holistic solutions—a situation that continues today. The results and deficiencies of past bad and good practices in these two compared EU member states might offer some further reflections on possible steps to follow or avoid regarding active ageing solutions in the EU.